2021
DOI: 10.3390/pathogens10010060
|View full text |Cite
|
Sign up to set email alerts
|

Lower Levels of Transaminases but Higher Levels of Serum Creatinine in Patients with Acute Hepatitis E in Comparison to Patients with Hepatitis A

Abstract: In patients with hepatitis E virus (HEV) infections, extrahepatic, particularly renal and hematological manifestations, are increasingly reported in the medical literature but have never been studied compared to a control cohort. We retrospectively analyzed medical records of consecutive patients that were diagnosed with acute hepatitis E (AHE) (n = 69) or acute hepatitis A (AHA) (n = 46) at the University Medical Center Hamburg Eppendorf from January 2009 to August 2019 for demographical, clinical, and labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…It has previously been shown that renal function is slightly deteriorated in the setting of acute HEV genotype 3 infection [6]. Furthermore, a complex interplay of immune cells and renal epithelium with acute kidney injury in HEV genotype 1 infections has been shown [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been shown that renal function is slightly deteriorated in the setting of acute HEV genotype 3 infection [6]. Furthermore, a complex interplay of immune cells and renal epithelium with acute kidney injury in HEV genotype 1 infections has been shown [12].…”
Section: Discussionmentioning
confidence: 99%
“…Large cohort studies investigating an association between HEV infections and renal diseases are still lacking. However, recently it has been described that patients with HEV infections have a reduced kidney function in comparison to patients with hepatitis A virus infections [6].…”
Section: Introductionmentioning
confidence: 99%
“…HEV infection has been associated with immune-mediated kidney diseases [ 86 ] even in immunocompetent patients [ 87 ], and AKI occurred in 8.6% in a cohort study [ 88 ]. Renal disease in acute HEV infection cases was slightly worse than in HAV infection cases [ 89 ]. HEV genotype 1, and HEV genotype 3 especially, have been strongly associated with renal disease [ 83 , 90 ].…”
Section: Hepatitis Virusesmentioning
confidence: 99%
“…Metabolites of the virus may invade the wall of the gallbladder or biliary epithelial cells, leading to cholestasis, which in turn results in acalculous cholecystitis (10,25). The extrahepatic manifestations of HE reported to date mainly include acute pancreatitis (26), neurological diseases (27,28), kidney injury (29), and hematologic disorders (30,31). HE-related cholecystitis was not reported in a study from Qatar until 2009; however, there were only two cases (32).…”
Section: Introductionmentioning
confidence: 99%